Les nouvelles provinces de la République Démocratique du Congo : construction territoriale et ethnicités - Jean-Claude Bruneau (L'Espace Politique)
The purpose of this article is to question the recent regionalization of a quasi federal type which has been chosen by the DRC, and its ability to prevent any force from dividing up this vast country. It would appear that this process of construction and deconstruction of territories has been going on far over a century. That the 26 new provinces, the framework of which is very old, draw their spatial and human structure from a logic that is clearly one of identity. That the principle of cutting up regional areas, as well as its results on the ground, and the political style of the system, arouse harsh criticisms. And above all, that even if the national conscience is a genuine reality, the feeling of ethnicity is also very strong, and needs to be tamed in order to solidly rebuild a united Congo.